Problems of teachers' Profession at Grade V SD 11 Lolong Ulak Karang - Gusnita Efrina; Nofriza Efendi; Nadiatul Rahma; Kholijah Hasni Daulay; Sela Febriani; Feronika Situmorang; Dira Putri (The Future of Education Journal, 2023)
Teacher professionalism is often associated with three important factors, namely competence, certification and professional allowance. These three factors are predicted to affect the quality of education. Considering that research results do not yet support such a frame of mind, 3 issues related to teacher certification were born, namely: improving student learning outcomes taught by post-certification teachers, low quality of learning processes taught by post-certification teachers and less professional teacher behavior. Therefore it is necessary to develop post-certification teachers which must be carried out on an ongoing basis, due to the basic principle that teachers must be human learners (a learning person). As a professional teacher at SDN 11 Lolong and already holding an educator certificate, the teacher is obliged to continue to maintain his professionalism as a teacher. The development of teacher competence and professionalism can be carried out through efforts to foster and empower teachers. Thus it is necessary to conduct a more in-depth review of the teacher certification program at SDN 11 Lolong in position, especially the purpose and meaning of certification, efforts to improve the teacher's mind set and a program of care and professional development for teachers who have passed the certification program, especially in efforts to improve the quality of learning services. Post-certification development of SDN 11 Lolong teachers' professionalism requires management competencies, empowerment strategies, development supervision, and classroom action research